Design happy : colorful homes for the modern family - Wentz, Betsy (Gibbs Smith, 2023)
"In her first book, interior designer Betsy Wentz shares 13 fabulous family homes. The book is really a practical design guide for anyone who may not want--or simply cannot afford--to hire an interior designer. The story of each home includes color studies, design lessons, and pro tips, plus plenty of practical advice for anyone who might face similar challenges"--